Implementation of Collaborative Learning Models in Indonesian Subject at Universities - Purwati Zisca Diana; Roni Sulistiyono; Rizka Abri Pradani (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2019)
The purpose of this study was to determine the effectiveness of implementing collaborative learning models. This study uses a quasi-experimental research method. The instrument used in this study is a collaborative assessment sheet filled by yourself, friends, and groups. The subjects in this study were 84 students divided into classes 2A and 2B of Guidance and Counseling study programs, Teacher Training and Education Faculty, Ahmad Dahlan University, Yogyakarta. Based on the results of the study, the collaborative ability of class 2B Guidance and Counseling Study Program, Teacher Training and Education Faculty, Ahmad Dahlan University Yogyakarta, as an experimental class, experienced an increase in the predicate already consistent (SB) from 0% to 57.14%; the predicate starts consistently (B) from 0% to 26.19%; the predicate has not been consistent (C) has improved with a decrease in the percentage from 76.19% to 11.91%; and the inconsistent predicate (K) also improved with a decrease in percentage from 23.81% to 4.76%. The collaborative ability of class 2A students in the Guidance and Counseling Study Program, the Teacher Training and Education Faculty, Ahmad Dahlan University Yogyakarta, as a control class, has increased the predicate already consistent (SB) from 0% to 26.32%; the predicate starts consistently (B) from 0% to 31.58%; the predicate has not been consistent (C) has improved with a decrease in percentage from 76.32% to 34.21%; and the inconsistent predicate (K) also improved with a decrease in percentage from 23.68% to 7.89%.